Generation of a Transplantable Population of Human iPSC-Derived Retinal Ganglion Cells - Rabesandratana, Oriane; Chaffiol, Antoine; Mialot, Antoine; Slembrouck-Brec, Amélie; Joffrois, Corentin; Nanteau, Céline; Rodrigues, Amélie; Gagliardi, Giuliana; Reichman, Sacha; Sahel, José-Alain; Chédotal, Alain; Duebel, Jens; et al. (Frontiers in Cell and Developmental Biology, 2020)
Optic neuropathies are a major cause of visual impairment due to retinal ganglion cell (RGC) degeneration. Human induced-pluripotent stem cells (iPSCs) represent a powerful tool for studying both human RGC development and RGC-related pathological mechanisms. Because RGC loss can be massive before the diagnosis of visual impairment, cell replacement is one of the most encouraging strategies. The present work describes the generation of functional RGCs from iPSCs based on innovative 3D/2D stepwise differentiation protocol. We demonstrate that targeting the cell surface marker THY1 is an effective strategy to select transplantable RGCs. By generating a fluorescent GFP reporter iPSC line to follow transplanted cells, we provide evidence that THY1-positive RGCs injected into the vitreous of mice with optic neuropathy can survive up to 1 month, intermingled with the host RGC layer. These data support the usefulness of iPSC-derived RGC exploration as a potential future therapeutic strategy for optic nerve regeneration.